2023
DOI: 10.17221/180/2022-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Using precision livestock farming for dairy herd management

Abstract: The aim of this study was to validate selected precision livestock farming (PLF) methods of nutrition and feeding management of high-yielding Holstein dairy cows. In a feeding trial with 36 dairy cows, the effect of replacing 0.1 kg of sodium bicarbonate in the control total mixed ration (TMR-C) with 1 kg of wheat straw in the experimental total mixed ration (TMR-S) on the physiological status of cows and the amount of milk produced (milk yield, MY) was investigated. Feed intake time (FT), as measured using te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
2
2
Order By: Relevance
“…The highest positive correlation (r = 0.63) was found between FT (TFT) and FT (NC), although only at a moderate level [ 39 ]. These values are higher than those obtained in our previous experiment [ 18 ], where FT (TFT) was correlated with FT (NC) at r = 0.27. Logically, MY increased with the amount of TMR consumed (r = 0.451), and the correlation coefficient (r = 0.55) was higher in our previous experiment [ 18 ].…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…The highest positive correlation (r = 0.63) was found between FT (TFT) and FT (NC), although only at a moderate level [ 39 ]. These values are higher than those obtained in our previous experiment [ 18 ], where FT (TFT) was correlated with FT (NC) at r = 0.27. Logically, MY increased with the amount of TMR consumed (r = 0.451), and the correlation coefficient (r = 0.55) was higher in our previous experiment [ 18 ].…”
Section: Discussioncontrasting
confidence: 89%
“…These values are higher than those obtained in our previous experiment [ 18 ], where FT (TFT) was correlated with FT (NC) at r = 0.27. Logically, MY increased with the amount of TMR consumed (r = 0.451), and the correlation coefficient (r = 0.55) was higher in our previous experiment [ 18 ]. Stone et al [ 42 ] reported a weak correlation (r = 0.22) between RT and daily MY.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations